Topology optimization strategies for a formula student concept - Delgado, Tiago Miguel Sequeira (2020)
With several applications in a wide scope of engineering problems, topology optimization has found a niche in the automotive industry, which, despite being a relatively new technology, has subsequently been implemented in strategic systems at early development stages as to find novel structural solutions to key problems whose solutions had been stagnating in the industry. In this work, the process of implementing the topology optimization process in Formula Student car systems was analyzed, as it is seen as the prime example for research work in the automotive world outside of the automotive sector industry itself. Thus, a design process was developed encompassing several phases, from: (i) workload influence assessments, (ii) mesh refinement and target volume influences and (iii) strategies to correctly translate TO results to NURBS structures. Additionally, a series of strategies to enhance the manufacturability of topology optimization results were developed, with emphasis on promoting the use of milling operations, as to evaluate future applications which the industry could initiate, as at this moment it is primarily focused in small series parts in high end models. In order to achieve these goals, the Solidworks 2019 software was utilized, specifically the topology optimization add-on, which utilizes a Solid Isotropic Material with Penalization (SIMP) approach, with its benefits and caveats discussed throughout the work.